Enhancing Livestock Sector Simulation: Synergizing Dynmod and Multimarket Models with Female Sexed Artificial Insemination as a Policy Scenario - Maruta, Admasu Asfaw; Bahta, Sirak T.; Enahoro, Dolapo K.; Baltenweck, Isabelle (International Livestock Research Institute, 2024)
This paper explores the synergistic collaboration between two widely employed economic models—Dynmod and the multi-market partial equilibrium model SectorM—in the context of Tanzania's livestock sector. Dynmod excels in detailing intricate herd dynamics, while SectorM proficiently captures economic factors' dynamics. Recognizing the complementary strengths of these models, the research utilizes the General Algebraic Modeling System (GAMS) software to link Dynmod and SectorM, creating a more comprehensive simulation of Tanzania's livestock sector. The introduction of a reproductive shock, specifically female sexed artificial insemination (AI), serves as a critical test, aligning with AI's pivotal role in advancing genetic progress and overall herd management. Female sexed AI emerges as a strategic approach, optimizing production outcomes by selectively increasing the number of female cattle, enhancing milk production, and influencing economic dynamics. The paper highlights intuitive results from the model linkage, indicating a decrease in offtake animals, reduced meat production, and supply shock in SectorM, ultimately impacting prices and farmers' income in Tanzania's livestock sector. This research not only contributes to livestock sector modeling but also underscores the potential of female sexed AI as a strategic tool for policy interventions to enhance livestock production and improve the socioeconomic status of Tanzanian farmers.ed for Tanzania livestock sector simulations.